Comparison of Nonmesonic Hypernuclear Decay Rates Computed in Laboratory and Center-of-Mass Coordinates - De Conti, C. [UNESP]; Barbero, C.; Galeao, A. P.; Krmpotic, F. (Amer Inst Physics, 2014)
In this work we compute the one-nucleon-induced nonmesonic hypernuclear decay rates of He-5(Lambda), C-12(Lambda) and C-13(Lambda) using a formalism based on the independent particle shell model in terms of laboratory coordinates. To ascertain the correctness and precision of the method, these results are compared with those obtained using a formalism in terms of center-of-mass coordinates, which has been previously reported in the literature. The formalism in terms of laboratory coordinates will be useful in the shell-model approach to two-nucleon-induced transitions.
Keywords: Nonmesonic weak decay; Shell model formalism; Laboratory coordinates